A comparison of cholinesterase inhibitors in the treatment of quinuclidinyl benzilate-induced behavioural deficit in rats performing the multiple T-maze - Misík, Jan; Kassa, Jiří (Journal of Applied Biomedicine, 2014)
Cholinesterase inhibitors are beneficial in the treatment of Alzheimer's disease via indirect increase of cholinergic neuro-transmission. The aim of the present study was to evaluate the potency of inhibitors tacrine, rivastigmine and donepezil to reverse cholinergic depletion induced by 3-quinuclidinyl benzilate (QNB, 2 mg kg−1) in Wistar rats performing the multiple T-maze test. The effect of QNB on retention was compared to the effect of standard amnesic drug, scopolamine, at the dose of 0.3 mg kg−1. Well-trained rats were treated intra-peritoneally with QNB, followed by another injection containing saline or tacrine (10 mg kg−1) or rivastigmine (1.2 mg kg−1) or donepezil (2.65 mg kg−1) 15 min later. Rats were subjected to the T-maze task 30 min and 24 h following QNB administration. The passage time and number of errors were observed. QNB significantly impaired the performance of rats in both tested times in contrast to short-lasting effect of scopolamine (30 min only). The inhibitors rivastigmine and donepezil significantly attenuated QNB-induced behavioural impairment in the 30 min tests, whereas tacrine failed to have the same effect. Moreover, the performance of tacrine-treated rats was worse due to cholinergic over-stimulation. Beneficial effects of all tested inhibitors including tacrine were evident in the 24 h test.
Keywords: Synaptic Transmission; Spatial Navigation; Cholinesterase Inhibitors; Piperidines; Male; Rats, Wistar; prostorová navigace; Maze Learning; takrin; statistika jako téma; Phenylcarbamates; Alzheimerova nemoc; Alzheimer Disease; Indans; mužské pohlaví; potkani Wistar; Acetylcholine; piperidiny; nervový přenos; chinuklidinylbenzilát; bludiště - učení; krysa rodu Rattus; kognice; Animals; zvířata; Rats; indany; prostorové chování; acetylcholin; fenylkarbamáty; Spatial Behavior; Tacrine; Statistics as Topic; cholinesterasové inhibitory; Quinuclidinyl Benzilate; Cognition